ChemInform Abstract: Organosolv Pretreatment of Plant Biomass for Enhanced Enzymatic Saccharification. Issue 12 (March 2016) - Zhang, Zhanying; Harrison, Mark D.; Rackemann, Darryn W.; Doherty, William O. S.; O'Hara, Ian M.
Abstract: Review: 202 refs.